Dynamics of Inter-Group Communication in Tourism Management in Banda Neira - Ismy Wahyu Ismawaty; Adhi Kusuma; Ika Monika (International Journal Labs, 2025)
Banda Neira is one of the historical and cultural tourist destinations in Central Maluku which is one of the favorite destinations for foreigners. However, it is undeniable that Banda neira faces challenges in sustainable tourism management, including in communication. The dynamics of communication between groups, both between local communities, governments, and tourists, are key factors in the success of tourism management. This study aims to determine the dynamics of communication between groups in the context of tourism in Banda Neira as well as the obstacles in the dynamics of communication in Banda Neira. The method used in this study is qualitative descriptive with interview, observation, and documentation study techniques. The results of the study show that effective communication between groups results in good collaboration in environmental conservation and local cultural development. However, obstacles such as differences in interests, lack of trust, and lack of access to information hinder successful management.